Włosy w kobiecych narracjach lagrowych - Czarnecka, Barbara (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2018)
The article is the analysis of women’s lager narrations that reflect the procedure of shaving hair applied to female lager prisoners. It shows cultural, social and psychological meanings of this procedure, presents it as the element of the wide scale lager violence strategy, degradation ritual, the form of female identity and intimacy violation. Through the presentation of various circumstances in which women were shaved in concentration camps the text presents the situation complexity of the lager experience – its phases and the context. The article relates the variety of sources and includes the experiences of women of different nationalities, for example: German, Polish, Jewish.